Irreversible evolutionary loss of chitin‐degrading ability in the chitinase‐like protein Ym1 under positive selection in rodents. (22nd March 2023) - Okawa, Kazuaki; Tabata, Eri; Kida, Yuta; Uno, Kyohei; Suzuki, Hidetoshi; Kamaya, Minori; Bauer, Peter O.; Oyama, Fumitaka
Abstract: Ym1 (chitinase‐like 3, Chil3) expressed in mice is a nonenzymatic chitinase‐like protein, which shows 67% identity with mouse acidic chitinase (Chia). Similar to Chia, Ym1 is overexpressed in asthma and parasitic infections in mouse lungs. Due to the lack of chitin‐degrading activity, the biomedical role of Ym1 under these pathophysiological conditions remains to be determined. In this study, we investigated what region and amino acid changes in Ym1 resulted in the loss of enzymatic activity. Replacing two amino acids at the catalytic motif to obtain a Chia‐like sequence (N136D and Q140E; MT‐Ym1) did not activate the protein. We conducted a comparative study of Ym1 and Chia. We found that three protein segments—(i) the catalytic motif residues, (ii) exons 6 and 7, and (iii) exon 10—are responsible for chitinase activity loss in Ym1. We show that replacing each of these three segments in Chia that are also involved in substrate recognition and binding by the Ym1 sequence can fully abolish the enzymatic activity. In addition, we show that there have been extensive gene duplication events at the Ym1 locus specific to the rodent lineages. Consistent with this result, Ym1 orthologs from the rodent genome were under positive selection when analyzed through the CODEML program. These data suggest that numerous amino acid substitutions in the regions involved in the chitin recognition, binding, and degradation ability of the ancestor Ym1 molecule lead to the irreversible inactivation of the protein.